Academic libraries on the Creative Industries track: The perception of Spanish and Brazilian professionals - Sant-Geronikolou, Stavroula; Martínez-Ávila, Daniel [UNESP]; Koulouris, Alexandros (SAGE Publications, 2019)
As governments around the world are beginning to recognize the role of creativity in the promotion of innovation and competitive advantage in a Global Knowledge Economy (GKE), Creative Knowledge-based Industries are becoming the focus of attention. Nevertheless, and in spite of the rise of Big Data, the prevailing absence of systematic library collection of activity data perpetuates the persistence of traditionalist and myopic approaches that tend to overlook the nexus between libraries and creativity while perceiving libraries as exclusively or basically collection gatekeepers, information brokers, and content providers. Given the universally acknowledged fact that the central value of the library is clearly creative, we embarked on the exploration of the academic library position within the Creative Industries system, as seen through the Ibero-American library community lens. In this vein, and following a literature review that focused on the interpretation of the intensity of libraries' creative value and content across different Creative Industries classification models, our survey within the library expert community attempts to investigate the relationship between academic libraries and the creative industries (CI) realm. Our overarching goal is to facilitate the articulation of targeted recommendations and to contribute to the conceptual foundations guiding the formation of a special interest group that will streamline the academic librarianship community response to this challenging area.
Keywords: Academic libraries; Brazilian libraries; creative industries; creativity; knowledge-intensive professions; Spanish libraries; value co-creation